2015
DOI: 10.11604/pamj.2015.20.8.5042
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome de Gougerot-Sjögren primitif du sujet âgé: caractéristiques cliniques et immunologiques

Abstract: Les objectifs de notre étude est d’étudier les caractéristiques cliniques et immunologiques du syndrome de Gougerot Sjogren primitif (SGSp) du sujet âgé et les comparer à une population témoin plus jeune. Nous avons analysé rétrospectivement les dossiers de 60 patients atteints de SGSp consécutifs, suivis au service de Médecine interne du CHU Taher Sfar de Mahdia, en Tunisie, durant une période de 7 ans (janvier 2007 à décembre 2013). Les patients avec SGSp étaient classés en deux groupes selon l’âge de début … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Its prevalence increases with age with a variable rate according to the literature. Indeed, the frequency was 30% according to Haga and [12] and was higher with 6% to 20% in other studies [10] [18] [19]. SS predominates in women with a female/male sex ratio of 9/1 or more [10] [11] [18] [19].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Its prevalence increases with age with a variable rate according to the literature. Indeed, the frequency was 30% according to Haga and [12] and was higher with 6% to 20% in other studies [10] [18] [19]. SS predominates in women with a female/male sex ratio of 9/1 or more [10] [11] [18] [19].…”
Section: Discussionmentioning
confidence: 96%
“…In Senegal, a study in a rheumatology department reported 74 cases of connective tissue disease in the elderly in 5 years [5]. Several studies have been carried out on the particularities of RA in the elderly [6] [7] [8] [9] and other studies have concerned SS [10] [11] [12] and systemic lupus erythematosus in the elderly [13] [14] [15] [16] and often the aspects of these affections were compared with those of the adults [17] [18] [19]. Our present study aimed to determine the clinical and paraclinical characteristics of systemic autoimmune diseases in the elderly in internal medicine in Dakar.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently involved organs were joints (85.0%), nervous system (28.3%), and lungs (23.3%). 23 In the second largest series from Morocco, the most frequently involved organs in the 57 patients with pSS were joints (87.7%), lungs (28.1%), and nervous system (17.5%), with 50 (87.7%) patients complaining of severe fatigue. Neither rates of glandular involvement nor findings on salivary gland biopsy or results of the Schirmer test were specified.…”
Section: Glandular Extraglandular and Autoantibody Featuresmentioning
confidence: 97%
“…13,17,18,[21][22][23]25,27 In the largest series, antinuclear antibodies, anti-Ro/SS antigen A (SSA), and anti-La/SS antigen B (SSB) antibodies were found in 42 (70%), 35 (58.3%), and 22 (36.7%) patients, respectively. 23 In the second largest series, anti-Ro/SSA and anti-La/SSB autoantibodies were reported in 44 (77.2%) and 46 (80.7%) patients, respectively. 17 In another Tunisian study involving 31 patients (20 pSS/11 sSS), 18 (69.3%) of 26 patients tested had both anti-Ro/ SSA and anti-La/SSB antibodies.…”
Section: Glandular Extraglandular and Autoantibody Featuresmentioning
confidence: 99%
“…EOpSS has an estimated overall prevalence of approximately 3%, but epidemiological data are very heterogeneous, depending on variables such as geographic area and diagnostic criteria. As an example, in an Italian cohort, 6% of patients had EOpSS [16], while in a Tunisian cohort this value was 30% [17].…”
Section: Introductionmentioning
confidence: 98%